Browse or browsing: Investigating goat preferences for feeding posture, feeding height and feed type - Cellier, Marjorie; Nielsen, Birte L.; Duvaux-Ponter, Christine; Freeman, Hannah B. R.; Hannaford, Rina; Murphy, Briar; O'Connor, Emma; Cote, Kevan R. L.; Neave, Heather W.; Zobel, Gosia (Frontiers in Veterinary Science, 2022)
Goats naturally browse different forages in various postures; this differs from typical farm practice, thus there are opportunities to improve goat welfare by understanding what and how they like to eat. We investigated if feeding preference was related to posture, feeder height relative to the ground, and type of feed. Sixteen adult, Saanen cross females participated in two experiments comparing a floor-level feeder (grazing posture; farm standard), with an elevated feeder (browsing posture; Exp1) and a platform-level feeder (raised, grazing posture; Exp2), when two forages (leaves, grass) were offered. Measurements included feed intake (g of DM/feeder), feeder switching frequency, first feeder visited, latency to visit first feeder and exploration and non-feeding activity time. Effects of posture (Exp1), height (Exp2) and feed type were analyzed. Type of feed affected preference for feeding posture and height. All goats consumed leaves over grass (Exp1: POP: 188 ± 6.52g, GRA: 20.3 ± 7.19g; Exp2: POP: 191 ± 6.15g, GRA: 0.231 ± 6.91g; P<0.001), and the feeder containing leaves was often visited first (Exp 1: GRA/POP: 94% of visits, P<0.001, POP/GRA: 53%, P=0.724; Exp 2: GRA/POP: 91%, P<0.001; POP/GRA: 69%, P=0.041). When goats received only leaves, they consumed more from the floor-level (162 ± 22.2g) vs elevated level (102 ± 21.9g) feeder (P=0.039). When goats received only grass, there was no posture or height preference; however, they changed feeders more frequently (at least 4x (Exp1) and 2x (Exp2) more than other combinations; P>0.01). Feed intake was negatively affected by exploring time (Exp1 only: r = -0.541; P<0.001) and performing non-feeding activities (Exp1: r = -0.698; P<0.001; Exp2: r = -0.673; P<0.001). We did not identify a preference for elevated feeding posture; however, we suggest that our short test (compared to previous work) encouraged goats to make choices based on line-of-sight and also that the elevated feeder design (replicated from previous work) made leaf access harder. Nonetheless, we highlight that some goats actively used the elevated feeder; this coupled with the clear preference for leaves over grass, suggests that offering feed type and presentation diversity would allow individuals to express their natural feeding behavior more fully.